Evaluation of vitamin and mineral content of commercial premixes - Süleyman Tekelioğlu; Emel Gürbüz; Behiç Coşkun; Fatma İnal (Eurasian Journal of Veterinary Sciences)
Aim: This research was conducted to determine vitamin and mineral content in commercial premixes and trace minerals and heavy metals content of trace mineral sources which are used in premixes. Materials and Methods: Research was carried out as two experiments. Ten pieces of poultry and ruminant premixes were collected and vitamin, mineral and heavy metal analyses were done in experiment 1. Raw materials of trace mineral sources as iron (Fe), zinc (Zn), copper (Cu) and manganese (Mn) were collected from 6 companies and trace mineral and heavy metals as cadmium (Cd), lead (Pb) analyses were done in experiment 2. Results: Vitamin and mineral values of poultry and ruminant premixes was lower than declared values in experiment 1. There were no heavy metals in trace mineral sources in experiment 2. Conclusion: Differences between declared values of vitamins and result of analysis should be depending on storage and inorganic trace minerals effects.